A journey towards sustainable feedback. Issue 2 (17th February 2018) - Mutch, Allyson; Young, Charlotte; Davey, Tamzyn; Fitzgerald, Lisa
Abstract: Meeting students' expectations associated with the provision of feedback is a perennial challenge for tertiary education. Efforts to provide comprehensive, timely feedback within our own first year undergraduate public health courses have not always met students' expectations. In response, we sought to develop peer feedback activities to support the development of 'self-evaluative strategies' that would acknowledge the centrality of students in the feedback process. We describe these activities, their staged development and the qualitative and quantitative data gathered from students and the teaching teams to evaluate this. Our first steps towards embedding peer feedback with first year students indicated they are willing to engage in the process and appreciated the opportunity to provide and receive feedback, but the quality and extent of the peer feedback was largely superficial. Students' reflections on the feedback received were also shallow. Supporting students to develop self-evaluative skills cannot be achieved in the short term, but must be embedded in courses and consistently reinforced, with greater emphasis placed on the development of a dialogue around feedback that connects students with peers and educators.